Dinamika Kehidupan Perempuan Hunian Tetap “Dongkelsari” Gungan Wukirsari Satu Dasawarsa Pasca Erupsi Merapi - Leslie Retno Angeningsih, Sri Utami, Anastasia Adiwirahayu (Program Studi Pembangunan Masyarakat Desa (D3), 2021)
A planned and involuntary relocation for post-disaster reconstruction has become a government policy in many developing countries in recent decades. Several studies have shown that relocation has a negative impact, especially on women. This study aims to examine how the dynamics of women’s lives in Huntap Dongkelsari, Gungan, Wukirsari Sleman, a decade post-Merapi eruption? This study used a qualitative descriptive method, and data were collected through observation, in-depth interviews, and documentation. The total number of informants is 21 people, selected purposively consisting of the Village Head, Village Secretary, the Head of Padukuhan, the Head of PKK, village women activists, and housewives. The data analysis technique used a descriptive-interpretative. To test the validity through the convergence of information from various sources used triangulation techniques. The results showed that after a decade of living in Huntap, women’s lives are very dynamic, and the problems facing become more complicated. Even though women mostly were grateful for having new places for their families but some were still disappointed. Relocation had made the changing in women’s roles and statuses; their economic conditions; their expenses for water and trash; the hard situation encourages women’s creativity in maximizing space; but created some problems with neighbors on privacy; children’s activities; children’s need for a place of residence. One thing that remains unchanged is the solidarity and sense of attachment among neighbors or social capital which is kept and nurtured since at temporary resettlement (Huntara). Women’s opportunities to gain access to the facilities, and information to achieve equality and reduce the double burden are needed